Scaling behaviour and rate-determining steps in filamentous self-assembly. Issue 10 (31st August 2017) - Meisl, Georg; Rajah, Luke; Cohen, Samuel A. I.; Pfammatter, Manuela; Šarić, Anđela; Hellstrand, Erik; Buell, Alexander K.; Aguzzi, Adriano; Linse, Sara; Vendruscolo, Michele; Dobson, Christopher M.; Knowles, Tuomas P. J.
Abstract : A general reaction network for filamentous self-assembly unifies mechanistic descriptions and links the overall scaling behaviour to the underlying rate-determining steps. Abstract : The formation of filaments from naturally occurring protein molecules is a process at the core of a range of functional and aberrant biological phenomena, such as the assembly of the cytoskeleton or the appearance of aggregates in Alzheimer's disease. The macroscopic behaviour associated with such processes is remarkably diverse, ranging from simple nucleated growth to highly cooperative processes with a well-defined lagtime. Thus, conventionally, different molecular mechanisms have been used to explain the self-assembly of different proteins. Here we show that this range of behaviour can be quantitatively captured by a single unifying Petri net that describes filamentous growth in terms of aggregate number and aggregate mass concentrations. By considering general features associated with a particular network connectivity, we are able to establish directly the rate-determining steps of the overall aggregation reaction from the system's scaling behaviour. We illustrate the power of this framework on a range of different experimental and simulated aggregating systems. The approach is general and will be applicable to any future extensions of the reaction network of filamentous self-assembly.